2019
DOI: 10.3310/hta23450
|View full text |Cite
|
Sign up to set email alerts
|

A contingency management intervention to reduce cannabis use and time to relapse in early psychosis: the CIRCLE RCT

Abstract: Background Cannabis is the most prevalent illicit substance among people with psychosis, and its use is associated with poorer clinical and social outcomes. However, so far, there has been limited evidence that any treatment is effective for reducing use. Contingency management (CM) is an incentive-based intervention for substance misuse that has a substantial evidence base across a range of substances and cohorts. However, to date there have been no randomised controlled trials (RCTs) of CM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 68 publications
2
22
0
Order By: Relevance
“…Our results showed that the type and intensity of face-to-face psychological interventions for CUD were variable and depended on clinicians' training background, skills, and experience. Similar to previous studies, we found that structural factors (ie, lack of time and staff turnover) represent barriers to psychological interventions [13,28]. Clinicians viewed TBPIs as a useful addition to their toolbox of interventions and as a way to circumvent some of these barriers and increase the consistency of services offered in FEP clinics.…”
Section: Principal Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…Our results showed that the type and intensity of face-to-face psychological interventions for CUD were variable and depended on clinicians' training background, skills, and experience. Similar to previous studies, we found that structural factors (ie, lack of time and staff turnover) represent barriers to psychological interventions [13,28]. Clinicians viewed TBPIs as a useful addition to their toolbox of interventions and as a way to circumvent some of these barriers and increase the consistency of services offered in FEP clinics.…”
Section: Principal Findingssupporting
confidence: 85%
“…Therefore, using CM only in conjunction with other psychological interventions (eg, MI, CBT, or psychoeducation) was considered potentially beneficial in achieving long-term reductions in cannabis use. This opinion is empirically supported by recently published data from the Contingency Intervention for Reduction of Cannabis in Early Psychosis randomized controlled trial (RCT), which showed that cannabis use and abstinence rates were not statistically different between the CM and computer-based psychoeducation intervention arms at 3-and 18-month follow-ups [28,31]. Our results suggest that offering nonfinancial incentives as part of the TBPIs could be considered a strategy to increase patient engagement in the intervention, are social reinforcement techniques (eg, certificates for achieving treatment milestones), and are generally appreciated by individuals receiving interventions for SUD [32,33].…”
Section: Principal Findingsmentioning
confidence: 74%
“…There is a paucity of literature examining evidence-based treatment for substance use among individuals experiencing early psychosis (Bello & Dixon, n.d.). A recent study found that contingency management did not reduce cannabis use among individuals with FEP enrolled in an early intervention program (Johnson et al, 2019; Rains et al, 2019). However, previous studies have demonstrated the effectiveness of contingency management on increasing abstinence from alcohol, tobacco, and cannabis among individuals with co-occurring substance use and serious mental illness in an array of treatment settings (Forster et al, 2019; McPherson et al, 2018; Oluwoye, Kriegel, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is limited evidence in relation to clinical interventions for cannabis psychosis, and although some are in the development stage, these tend to be focused on a specific symptom of psychosis such as thoughts rather than targeting all aspects of the condition [32,33,34]. There are encouraging signs that a cognitive based model could be used to treat those who have developed a cannabis psychosis [35].…”
Section: Interventions For Cannabis Psychosismentioning
confidence: 99%